Healthy and sustainable diets for future generations - Green, Hilary (J Sci Food Agric, 2018)
Global food systems will face unprecedented challenges in the coming years. They will need to meet the nutritional needs of a growing population and feed an expanding demand for proteins. This is against a backdrop of increasing environmental challenges (water resources, climate change, soil health) and the need to improve farming livelihoods. Collaborative efforts by a variety of stakeholders are needed to ensure that future generations have access to healthy and sustainable diets. Food will play an increasingly important role in the global discourse on health. These topics were explored during Nestlé's second international conference on ‘Planting Seeds for the Future of Food: The Agriculture, Nutrition and Sustainability Nexus’, which took place in July 2017. This article discusses some of the key issues from the perspective of three major stakeholder groups, namely farming/agriculture, the food industry and consumers. © 2018 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.